Stability of a magnetically levitated nanomagnet in vacuum: Effects of gas and magnetization damping - Kustura, Katja; Wachter, Vanessa; Lopez, Adrian E. Rubio; Rusconi, Cosimo C. (Physical Review B, 2022)
In the absence of dissipation a nonrotating magnetic nanoparticle can be stably levitated in a static magnetic field as a consequence of the spin origin of its magnetization. Here we study the effects of dissipation on the stability of the system, considering the interaction with the background gas and the intrinsic Gilbert damping of magnetization dynamics. At large applied magnetic fields we identify magnetization switching induced by Gilbert damping as the key limiting factor for stable levitation. At low applied magnetic fields and for small particle dimensions, magnetization switching is prevented due to the strong coupling of rotation and magnetization dynamics, and the stability is mainly limited by the gas-induced dissipation. In the latter case, high vacuum should be sufficient to extend stable levitation over experimentally relevant timescales. Our results demonstrate the possibility to experimentally observe the phenomenon of quantum spin stabilized magnetic levitation.
CRIS-Team WoS Importer:2022-08-12